RISK FACTORS OF BREAST CANCER AMONG WOMEN IN AKOKO SOUTH WEST LOCAL GOVERNMENT AREA OF ONDO STATE - BABATUNDE, OBALASE, STEPHEN; BOLANLE, OGBEYE GBEMISOLA; CLEMENT, ADELUSI; OMOTOLA, ADELUSI RACHAEL (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The current study was designed to investigate the risk factors of breast cancer among women in Akoko South West Local Government Area of Ondo state. Questionnaire was the research instrument. Two research questions and two hypotheses were raised in the study. Data were gathered using a questionnaire which was subjected to face and content validity by expert in education. The reliability value of Pearson product moment correlation was 0.93 which indicated that the instrument was reliable before it was administered on the respondents. The study involved 200 respondents which were randomly selected. Data collected from the respondents were subjected to statistical analysis using simple percentage, chi-Square and correlation. Analysis of the data revealed that Socio – Economic Cultural and Demographic factors such as age, travel distance to screening facility, cost of screening, most cultural practices and socio – commitments have significant negative correlation with breast cancer screening uptake. However, marital status, educational level, socio – economic status, most religious practices and socio – cultural factors have a significant positive association with breast cancer screening uptake. Psychosocial variables such as fear, anticipated pain and discomfort, stigma and concern for embarrassment were found to be significantly associated to breast cancer screening uptake among the respondents. Institutional characteristics such as Breast Health Education, guidance and follow up by nurses on Breast Screening Examination, psychological care by the psychologist. Advertisements on breast cancer and screening have significant and positive correlation with breast cancer screening uptake.